Tinjauan Al-Qur’an Dan Sunah Tentang Mukjizat Para Nabi - Ine Ratu Fadliah (Program Pascasarjana UIN Sumatera Utara, 2022)
This research discusses the review of the Qur'an and Sunnah about the miracles of the prophets. The purpose of this study is to find out and analyze related to the review of the Qur'an and Sunnah about the miracles of the prophets. The method used in this study is a library approach. The results of this study indicate that miracles are extraordinary events or advantages beyond human reason that are not owned by anyone, because miracles are only given by Allah to His prophets and messengers. Meanwhile, if someone other than the prophets and apostles is given an extraordinary event by Allah, then it cannot be said to be a miracle, but it is a karomah. Ma'unah is the help given by Allah SWT to believers to overcome difficulties that, according to common sense, exceed their abilities. Ma'unah happens to ordinary people thanks to God's help. The function of miracles is to prove the truth of their claims as prophets. Therefore, an extraordinary deed is a miracle according to theology, if it is shown as an argument for the prophethood of a prophet, apart from the relation of the deed to the special permission of Allah SWT. If the meaning of the act is expanded again, it will include all extraordinary deeds which are proof of the truth of the claim to Imamat.